Microwave and Radio Frequency Heating in Food and Beverages - Koutchma, Tatiana N. (Elsevier, Academic Press, 2023)
Microwave and Radio Frequency Heating in Food and Beverages discusses advanced heating techniques based on electromagnetic and electro-technologies, including radiative or microwave (MW) dielectric heating, radio-frequency (RF) or capacitive dielectric heating, infrared (IR) heating, ohmic and magnetic induction heating. Unlike conventional systems where heat energy is transferred from a hot medium to a cooler product resulting in large temperature gradients, electro-heating involves the transfer of electromagnetic energy directly into the product, initiating volumetric heating due to frictional interaction between water molecules and charged ions (i.e., heat is generated within the product).